1996
DOI: 10.1016/0042-6989(96)00060-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-visual Information in Structure-from-motion

Abstract: We examined whether non-visual signals improve visual perception of three-dimensional structure-from-motion. Observers discriminated curvature in quadratic surfaces defined by random dot cinematograms with limited lifetime. They either explored visually a static surface by making head movements that were fed back to the display (HM condition) or they viewed statically the same surface which now rotated (NHM condition). Both conditions showed a clear build-up of performance as lifetime increases, but with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 13 publications
1
13
1
Order By: Relevance
“…According to current SFM models, the slant perceived at one moment in time is not influenced by the properties that the velocity gradients take on outside a small temporal window of about 200 ms that is necessary to measure the properties of the optic flow (e.g., Treue et al, 1991;van Damme & van de Grind, 1996). Contrary to this assumption, we found that judgments of surface slant covaried with the values Figure 20.…”
Section: Discussioncontrasting
confidence: 77%
“…According to current SFM models, the slant perceived at one moment in time is not influenced by the properties that the velocity gradients take on outside a small temporal window of about 200 ms that is necessary to measure the properties of the optic flow (e.g., Treue et al, 1991;van Damme & van de Grind, 1996). Contrary to this assumption, we found that judgments of surface slant covaried with the values Figure 20.…”
Section: Discussioncontrasting
confidence: 77%
“…The general emerging picture is that extraretinal information contributes to removing ambiguities in extraction of SFM surface parameters, such as curvature or orientation, helping to determine more reliable three-dimensional percepts (Cornilleau-Pérès & Droulez, 1994;S. Rogers & B. J. Rogers, 1992; van Damme & van de Grind, 1996;Wexler, Panerai, Lamouret, & Droulez, 2001 hand, few authors have pointed out a potential involvement of extraretinal signals in the calibration of motion parallax cues to recover absolute distance information (Bingham & Stassen, 1994;Eriksson, 1973Eriksson, , 1974. In the present investigation, we tested for experimental evidence of the role of extraretinal signals in the estimation of absolute distance.…”
mentioning
confidence: 99%
“…Once a particular surface point reached its maximal lifetime, it would Bdie^and be moved to a randomlydetermined location in the succeeding frame. Limiting the point lifetime is an effective way of introducing Bcorrespondence noise^into the stimuli: the lower the surface point lifetime, the more difficult the identification task (Norman, Dawson, & Butler, 2000;Todd, 1985;van Damme & van de Grind, 1996).…”
Section: Experimental Stimulimentioning
confidence: 99%